2010
DOI: 10.1111/j.1600-0501.2009.01903.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the visibility and the course of the mandibular incisive canal and the lingual foramen using cone‐beam computed tomography

Abstract: The high detection rate of the incisive canal and the lingual foramen in the anterior region of the mandible using CBCT indicates the potential high preoperative value of CBCT scan for surgical procedures in the anterior mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
3
17

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 32 publications
11
63
3
17
Order By: Relevance
“…These findings are in agreement with the results of Makris et al 4 (2010) and Rosa et al 34 (2013) that detected IC in 91% and 98.5% of cases respectively, using CBCT. According to Pires et al 37 (2012), the ICs could not be identified in all of the CBCT images due to the small diameter of this structure.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in agreement with the results of Makris et al 4 (2010) and Rosa et al 34 (2013) that detected IC in 91% and 98.5% of cases respectively, using CBCT. According to Pires et al 37 (2012), the ICs could not be identified in all of the CBCT images due to the small diameter of this structure.…”
Section: Discussionsupporting
confidence: 83%
“…A relatively precise knowledge of the location of this anatomical structure is of extreme importance prior to any surgical procedure in the region in order to avoid potential neurovascular complications 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary imaging techniques such as CBCT may be particularly suitable in the preoperative treatment planning. The MIC and LF is best seen in cross-sectional views (31) (Figure 3). …”
Section: Mandibular Incisive Canal and Lingual Foramenmentioning
confidence: 99%
“…The study suggested that the lingual foramen was a consistent finding to the lingual side of the mandible in the midline, being present in over 99% of the dried specimen examined. The foramen was definitely visible in 81% and 82% in Makris (Makris et al, 2010) based on CBCT and Jacobs (Jacobs et al,. 2002) based on CT studies, respectively.…”
Section: Importance Of Pre-surgical Assessmentmentioning
confidence: 99%